DIMENSI ZUHUD DALAM EKONOMI ISLAM - Riyandi Riyandi (University of Darussalam Gontor, 2013)
This paper tries to see the zuhud dimensions contained in Islamic economics al-Iqtisad al-Islamiy. To see it, here is explained the meaning of the zuhud in shar’i with tracing of lexical classical Arabic, the Qur’an and Sunah as well as the conception of the Ulama in particular in the Sufi tradition, and then linked to Islamic economics. From this discussion it was found that the Islamic economic discussion as al-Iqtisad al-Islamiy have epistemological implications derived from the revelation that the word iqtisad itself has meaning balance, not to exceed the limits or muqtasid. It shows that in Islamic economic there is zuhud dimension because the muqtasid people formed from zuhud attitude. In addition, the emphasis of Maqasid syari’ah that put Hifdz din as the main base shows that everything in economic activity should be done in terms of the religious dimension of faith, so that nothing is to be obtained not go beyond the rules set by God, and this rule can only be done by people who have the zuhud attitude to the world that makes bima fiyadillah awtsaq minhu bima fiyadihi.